Method for manufacturing repair material for packaging containing fine powder and repair material for packaging containing fine powder prepared thereby - FUGITA MIWAKO; MASUHARA HIROMASA; TASAKI ISAO (2018)
An objective of the present invention is to obtain a repair material which has satisfactory fluidity to improve viscosity degradation during repair, responds to various small repair portions such as cracks and holes including minute holes in a road repair surface or a waterproof layer, prevents a flash phenomenon at a high temperature in a summer season after construction, exhibits impact resistance, viscoelasticity, and plastic deformation in an early stage, and maintains satisfactory resistance, viscoelasticity, and plastic deformation for a long period of time. The repair material for paving containing fine powder is formed by mixing 10-30 wt% of waste lubricant liquid and lubricant, 0.5-3 wt% of synthetic silica, 35-55 wt% of blown asphalt with a penetration of 10-30, 12-30 wt% of straight asphalt with a penetration of 100-200, 1-4 wt% of rosin, 12-25 wt% of slaked lime, and 1-6 wt% of bentonite. 본 발명은, 보수시에 있어서의 점성의 나쁨을 개선하기 위하여 유동성을 양호하게 하고, 도로보수면이나 방수층에 발생한 미세구멍을 포함하는 균열이나 구멍 등의 소규모의 각종 보수부분에 대응할 수 있고, 또한 시공 후에 있어서는 여름철 고온시의 플래시 현상을 방지하며, 내충격성, 점탄성, 소성변형 등을 조기에 발휘하고, 그들이 장기간에 걸쳐 양호한 상태를 유지할 수 있는 보수재를 얻는 것을 목적으로 하는 것이다. 윤활유폐액 및 윤활유 10~30중량%, 합성실리카 0.5~3중량%, 침입도 10~30의 블로운 아스팔트 35~55중량%, 침입도 100~200의 스트레이트 아스팔트 12~30중량%, 로진 1~4중량%, 소석회 12~25중량%, 벤토나이트 1~6중량%를 혼합하여 이루어지는 것을 특징으로 하는 미분체 함유 포장용 보수재.